2008
DOI: 10.1074/jbc.m802132200
|View full text |Cite
|
Sign up to set email alerts
|

G9a-mediated Lysine Methylation Alters the Function of CCAAT/Enhancer-binding Protein-β

Abstract: The functional capacity of the transcriptional regulatory CCAAT/enhancer-binding protein-␤ (C/EBP␤) is governed by protein interactions and post-translational protein modifications. In a proteome-wide interaction screen, the histone-lysine N-methyltransferase, H3 lysine 9-specific 3 (G9a), was found to directly interact with the C/EBP␤ transactivation domain (TAD). Binding between G9a and C/EBP␤ was confirmed by glutathione S-transferase pulldown and co-immunoprecipitation. Metabolic labeling showed that C/EBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 56 publications
0
97
1
1
Order By: Relevance
“…C/EBP␤ transcription efficacy can be regulated by lots of post-translational modifications, including phosphorylation (31,32), SUMOylation (33), acetylation (34), and methylation (35). In addition, it has been shown that phosphorylation of C/EBP␤ can abrogate its methylation by protein-arginine methyltransferase 4 PRMT4/CARM1, thus demonstrating the cross-talk between phosphorylation and epigenetic methylation of C/EBP␤ (36).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBP␤ transcription efficacy can be regulated by lots of post-translational modifications, including phosphorylation (31,32), SUMOylation (33), acetylation (34), and methylation (35). In addition, it has been shown that phosphorylation of C/EBP␤ can abrogate its methylation by protein-arginine methyltransferase 4 PRMT4/CARM1, thus demonstrating the cross-talk between phosphorylation and epigenetic methylation of C/EBP␤ (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that phosphorylation of Thr-220 triggers a cascade of events involving abrogation of the binding of the lysine methylase G9a and arginine methyl transferase PRMT4, thereby altering the pattern of covalent post-translational modifications, in particular the PRMT4-dependent methylation of arginine 3 of C/EBP␤. This, in turn, facilitates the recruitment of SWI/SNF chromatin remodeling and Mediator complexes by C/EBP␤ to ultimately increase the transcription of C/EBP␤ target genes (26,27,49). Our work suggests increased binding and phosphorylation of p300 as an alternative or additional mechanism by which the phosphorylation of C/EBP␤ at Thr-220 stimulates the transactivation potential of C/EBP␤.…”
Section: Discussionmentioning
confidence: 83%
“…The relative amounts of the different isoforms vary between different cell types and are influenced via a short upstream open reading frame by the status of the cell (11,(13)(14)(15). In addition to differential isoform expression, C/EBP␤, is regulated by posttranslational modifications, such as phosphorylation (16 -18), acetylation (19 -21), and sumoylation (22) as well as by the binding of specific cofactors via protein-protein interactions (23)(24)(25)(26)(27). Besides its function in normal cells, deregulation of C/EBP␤ activity or isoform expression contributes to the development of cancer (28 -31).…”
mentioning
confidence: 99%
“…Several nonhistone proteins can be methylated by G9a. The CCAAT/enhancer-binding protein-β (C/EBPβ) is methylated at K39, which may create a binding site for a repressive protein complex or enhance interaction with C/EBPβ by "reading" methylated K39 [12]. Lee et al [37] reported that reptin, a chromatin-remodeling factor, is methylated at K67 under hypoxic conditions by G9a.…”
Section: Lysine Methylation Of Nonhistone Proteinsmentioning
confidence: 99%
“…Moreover, increasing evidence indicates that nonhistone proteins are subject to reversible acetylation or methylation by histone-modifying enzymes. Among these nonhistone targets are transcription factors, hormone receptors, signal transducers, chaperones, and proteins of the cytoskeleton [6][7][8][9][10][11][12]. Although the acetylation of nonhistone proteins has been appreciated for some time [9,13,14], their methylation has been recognized only more recently.…”
mentioning
confidence: 99%